2018
DOI: 10.1504/ijbe.2018.093301
|View full text |Cite
|
Sign up to set email alerts
|

Does business model experimentation in dynamic contexts enhance value capture?

Abstract: Established theory suggests that firms experiment with business models in dynamic contexts. However, the relationship between business model experimentation and organizational performance remains unclear. Barriers to empirical analysis exist as experimental business models are normally utilised by new market entrants and the unit of analysis to test a business model in dynamic contexts extends beyond traditional firm boundaries. To overcome these barriers, we propose an assessment of the economic value of busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…The literature discusses sustainable management logic. In general, overcoming the traditional barriers and roles in management logic seems to be fundamental for the future of marketing strategies in this field (Vendrell-Herrero 2018 ). In particular, Kullak et al ( 2021 ) suggested that managers of minor organizations should develop and coordinate a network in which actors have access to relevant resources.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…The literature discusses sustainable management logic. In general, overcoming the traditional barriers and roles in management logic seems to be fundamental for the future of marketing strategies in this field (Vendrell-Herrero 2018 ). In particular, Kullak et al ( 2021 ) suggested that managers of minor organizations should develop and coordinate a network in which actors have access to relevant resources.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…The dynamics of continuous experimentation and focused learning, as revealed in this study, show that-by continuously experimenting with various business models-a frugally innovating enterprise is exposed to business model diversity. This enables it to better create, deliver and capture value, through full commitment to a business model that best serve customers with varying needs (Vendrell-Herrero et al, 2018). The proposition below then follows:…”
Section: Discussionmentioning
confidence: 99%
“…The extant literature suggests that, when emerging in dynamic contexts, firms are bound to experiment with different business models (Vendrell-Herrero, Parry, Opazo-Basáez, & Sanchez-Montesinos, 2018). Business model experimentation is a method for discovery driven, dynamic innovation around the business model, based on unknown assumptions, by testing and clarifying the results of the change (McGrath, 2010).…”
Section: Business Models and Frugal Innovationmentioning
confidence: 99%
“…The business model (BM) tends to be defined as the logic of how an organisation creates, delivers and captures value (Budler et al, 2021;Miller et al, 2021;Teece, 2018;Wirtz et al, 2016). More recently, it has been observed that this is far from a static process, with tight coupling of operating model and BM innovation concepts (Andreini et al, 2022;Bashir et al, 2020;Massa et al, 2017;Srai et al, 2022) and with firms increasingly engaging in BM redesign processes in dynamic industry contexts, where new capabilities and market challenges continuously emerge (Schaffer et al, 2019;Vendrell-Herrero et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…, 2022) and with firms increasingly engaging in BM redesign processes in dynamic industry contexts, where new capabilities and market challenges continuously emerge (Schaffer et al. , 2019; Vendrell-Herrero et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%